Bimonthly cassava (Manihot esculenta C.) leaf yield in relation to secondary infection of the crop by African Cassava Mosaic in the Provinces of Nord-Ubangi and Tshopo in the Democratic Republic of Congo - Médard, Molongo Mokondande; Sylvain, Solia Edondoto; Joseph, Litucha Bakokola; Godefroid, Monde te-Kazangba; Bénoît, Dhed'a Djaïlo (Budapest International Research and Critics University, 2023)
The present study aimed to evaluate the yield of cassava (Manihot et al.) leaves harvested bimonthly in relation to the level of secondary infection of the crop by MAM in Kisangani and Gbadolite respectively, in the provinces of Tshopo and Nord-Ubangi in the Democratic Republic of Congo. An experimental randomized complete block design was chosen, with 4 replicates and 5 treatments according to infection levels, including Level 0: No symptoms (apparently healthy subject); Level 1: Yellowish spots covering 1/5ème of the leaf blade (light mosaic); Level 2: Spots covering half the leaf blade, and appearance of leaf deformation (moderate mosaic); Level 3: Affected leaves deformed and partly curled up, vegetative apparatus reduced (strong mosaic); Level 4: Almost all leaf blades curled up, vegetative apparatus reduced (severe mosaic); Level 5: Leaves reduced to about 1/10ème of their surface area; on some, the leaf blade becomes non-existent, twigs very short, generally knotted, plant dies within a few months. Leaf yields recorded in Kisangani were in the order of 1.99 T/ha (Level zero, apparent absence of mosaic); 1.73 T/ha (Level 1, light mosaic); 2.13 T/ha (Level 2, moderate mosaic); 1.66 T/ha (Level 3, strong mosaic); 1.16 T/ha (Level 4, severe mosaic) with the Mbongo variety. On the other hand, at Gbadolite, 2.63 T/ha (Level zero, apparent absence of mosaic); 2.67 T/ha (Level 1, light mosaic); 3.01 T/ha (Level 2, moderate mosaic); 2.26 T/ha (Level 3, strong mosaic); 1.89 T/ha (Level 4, severe mosaic) were obtained with the Yasegumba variety. With the exception of levels 1 and 2, MAM caused yields to fall by 13.1 to 41.7% and 14.07 to 28.14% from level 1 (light mosaic) to level 4 (severe mosaic) by adopting bimonthly harvesting in Kisangani and Gbadolite respectively. This harvest is, therefore, one of the best techniques for managing MAM and producing leaves.